Significant Midlatitude Bubble‐Like Ionospheric Super‐Depletion Structure (BLISS) and Dynamic Variation of Storm‐Enhanced Density Plume During the 23 April 2023 Geomagnetic Storm - Ercha Aa; Shun‐Rong Zhang; Shasha Zou; Wenbin Wang; Zihan Wang; Xuguang Cai; Philip J. Erickson; Anthea J. Coster (Space Weather)
Abstract This paper investigates the midlatitude ionospheric disturbances over the American/Atlantic longitude sector during an intense geomagnetic storm on 23 April 2023. The study utilized a combination of ground‐based observations (Global Navigation Satellite System total electron content and ionosonde) along with measurements from multiple satellite missions (GOLD, Swarm, Defense Meteorological Satellite Program, and TIMED/GUVI) to analyze storm‐time electrodynamics and neutral dynamics. We found that the storm main phase was characterized by distinct midlatitude ionospheric density gradient structures as follows: (a) In the European‐Atlantic longitude sector, a significant midlatitude bubble‐like ionospheric super‐depletion structure (BLISS) was observed after sunset. This BLISS appeared as a low‐density channel extending poleward/westward and reached ∼40° geomagnetic latitude, corresponding to an APEX height of ∼5,000 km. (b) Coincident with the BLISS, a dynamic storm‐enhanced density plume rapidly formed and decayed at local afternoon in the North American sector, with the plume intensity being doubled and halved in just a few hours. (c) The simultaneous occurrence of these strong yet opposite midlatitude gradient structures could be mainly attributed to common key drivers of prompt penetration electric fields and subauroral polarization stream electric fields. This shed light on the important role of storm‐time electrodynamic processes in shaping global ionospheric disturbances.